Effectiveness and Contribution of Market Retributions to Regional Taxes in Parepare City - Jumriani Jumriani; Sariana Damis (Universitas Muhammadiyah Makassar, 2022)
Regional acceptance should be supported by the level of effectiveness. One of the things in the implementation of regional autonomy is Regional Taxes. The purpose of this study is to determine the level of effectiveness of market retibution management and the contribution of market retribution to the Regional Original Income (PAD) of Parepare City in 2016-2020. This research was carried out in Parepare City, precisely at the Office of the Regional Finance Agency. The data used in the study are primary data obtained through direct interviews with both staff and section heads in this case the market levy calculation section as well as traders. Data Analysis techniques using descriptive analysis, effectiveness ratio analysis and contribution ratio analysis. The results showed that the effectiveness of market levy receipts for Regional Taxes was effective in 2016-2018 , but in 2019-2020 it was less effective due to Covid-19 so that merchant income was reduced. The contribution of market retribution to the Regional Pajak is less contributing.